2021
DOI: 10.3390/healthcare9020222
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Psychological Impact of COVID-19 among College Students: An Evidence of 15 Countries

Abstract: Mental health issues among college students is a leading public health concern, which seems to have been exacerbated during the COVID-19 pandemic. While previous estimates related to psychological burden among college students are available, quantitative synthesis of available data still needs to be performed. Therefore, this meta-analysis endeavors to present collective evidence discussing the psychological impact of COVID-19 among college students. Bibliographical library databases, including Embase, Medline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
117
3
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(169 citation statements)
references
References 63 publications
(125 reference statements)
10
117
3
11
Order By: Relevance
“…Based on the evidence of individual studies, our study found a higher prevalence of mental health symptoms among frontline healthcare workers (37%, p<0.001) and university students (36%, p>0.001) than the general population and second-line responders (Batra et al, 2021; All rights reserved. No reuse allowed without permission.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Based on the evidence of individual studies, our study found a higher prevalence of mental health symptoms among frontline healthcare workers (37%, p<0.001) and university students (36%, p>0.001) than the general population and second-line responders (Batra et al, 2021; All rights reserved. No reuse allowed without permission.…”
Section: Discussionmentioning
confidence: 73%
“…The vulnerabilities of frontline healthcare workers are often attributed to higher risk of infection, burnout, fear of COVID-19 transmission to their family members, and job loss (Bhandari et al, 2021;Xiang et al, 2020). The greater prevalence of mental health symptoms among the university students can be explained by the uncertainties surrounding the course of the pandemic and the sudden transition to online education (Adedoyin & Soykan, 2020;Batra et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In this survey, 62.64% students had anxiety symptoms during the epidemic. Batra et al assessed the psychological impact of COVID-19 among college students and found that the prevalence of anxiety in China was 25.5% compared with 58.7% in other regions [27]. The government strengthened the management of information released, the frequency of news release conferences increased and information or knowledge acquisition methods were also added.…”
Section: Discussionmentioning
confidence: 99%
“…One meta-analysis of 27 studies from 15 countries, analyzing the psychological impact of COVID-19 among college students, showed a disproportionate burden of mental health problems among participants, with females having higher anxiety and depression levels than males. Increased stress, anxiety, and depressive symptoms were seen as a result of changes and uncertainty in university education, technological concerns about online courses, being far from home, social isolation, decreased family income, and future employment [32]. These impacts were also observed in universities across the world [33][34][35][36].…”
Section: Psychological Impact Of the Covid-19 Pandemic Among Higher-education Studentsmentioning
confidence: 99%
“…The eight items are as follows: [45]. The total depression subscale score was divided into scores for normal depression (0-9), mild depression (10-12), moderate depression (13)(14)(15)(16)(17)(18)(19)(20), severe depression (21)(22)(23)(24)(25)(26)(27), and extremely severe depression (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). The total anxiety subscale score was divided into five score categories: normal (0-6), mild anxiety (7-9), moderate anxiety (10-14), severe anxiety (15)(16)(17)(18)(19), and extremely severe anxiety .…”
Section: Phase I: Surveymentioning
confidence: 99%